Congruent representation of visual and acoustic space in the superior colliculus of the echolocating bat Phyllostomus discolor. (23rd September 2016) - Hoffmann, Susanne; Vega‐Zuniga, Tomas; Greiter, Wolfgang; Krabichler, Quirin; Bley, Alexandra; Matthes, Mariana; Zimmer, Christiane; Firzlaff, Uwe; Luksch, Harald
Abstract: The midbrain superior colliculus (SC) commonly features a retinotopic representation of visual space in its superficial layers, which is congruent with maps formed by multisensory neurons and motor neurons in its deep layers. Information flow between layers is suggested to enable the SC to mediate goal‐directed orienting movements. While most mammals strongly rely on vision for orienting, some species such as echolocating bats have developed alternative strategies, which raises the question how sensory maps are organized in these animals. We probed the visual system of the echolocating bat Phyllostomus discolor and found that binocular high acuity vision is frontally oriented and thus aligned with the biosonar system, whereas monocular visual fields cover a large area of peripheral space. For the first time in echolocating bats, we could show that in contrast with other mammals, visual processing is restricted to the superficial layers of the SC. The topographic representation of visual space, however, followed the general mammalian pattern. In addition, we found a clear topographic representation of sound azimuth in the deeper collicular layers, which was congruent with the superficial visual space map and with a previously documented map of orienting movements. Especially for bats navigating at high speed in densely structured environments, it is vitally important to transfer and coordinate spatial information between sensors and motor systems. Here, we demonstrate first evidence for the existence of congruent maps of sensory space in the bat SC that might serve to generate a unified representation of the environment to guide motor actions. Abstract : Here we demonstrate for the first time the existence of congruent sensory maps for visual and acoustic spatial information in the midbrain of a nocturnal and acoustically dominated mammal, the echolocating bat Phyllostomus discolor. Our novel data contribute to decode what functional role the superior colliculus, a midbrain nucleus primarily concerned with visuomotor transformation, plays in mediating orienting behavior in animals that mainly rely on auditory information for navigation.